Negotiating Identity, Navigating Dialogue: Friendship Preferences in Religious Streams - Ika Hana Pertiwi; Fadhil Maliky Islah; Muhamad Arif Saefudin; Wenty Marina Minza; F. A. Nurdiyanto (Balai Penelitian dan Pengembangan Agama Semarang, 2026)
Religious diversity in Indonesia extends beyond interreligious differences to include intra-religious sub-groups, often termed “streams” (aliran), distinguished by variations in rituals, congregations, religious symbols, and theological orientation (madhhab). While interreligious friendships have been widely studied, little is known about how individuals navigate intra-religious diversity in shaping friendship preferences. This study explores the relevance of religious streams in friendships to uncover preferences for engaging in same- or cross-group friendships within the same religion. This study was conducted by administering an online qualitative survey and analyzing the 131 valid responses using thematic analysis. Results indicate that most participants (89%) reported that religious streams did not influence their friendship preferences, expressing openness to friendships across different religious streams. However, a small proportion of participants expressed a preference for homophily or same-group friendship. The findings are presented into two themes: (1) preference for same-group friendships, reflecting homophily as a means for personal religious advancement; and (2) preference for cross-group friendship, characterized by pluralistic openness and religious dialogue navigation. As a synthesis, religious streams in friendship preferences reflect attitudes in negotiating the importance of social identity and navigating religious dialogue when engaging with religious matters. These two preferences should not be viewed as inherently contradictory; rather, they demonstrate the dynamic nature of religious life within pluralistic societies.